Synovial Matrix Remodeling and Inflammatory Profile in Disc Displacement of the Temporomandibular Joint: An Observational Case-Control Study - Pallavi Khattar; Mattias Ulmner; Henrike Häbel; Bodil Lund; Rachael V. Sugars (International Journal of Dentistry)
Conclusions: The observations confirmed differences in matrix remodeling and an increase in local inflammatory activity in the DDwoR diagnosis compared to the reference patient material, DDwR. The study highlighted the importance of synovial tissue characterization to unite micropathology and clinical findings, leading to more reliable diagnostic tools.